Investment Feasibility Analysis in Financial Aspects of Startup Business In Lifestyle Combining Barbershop And Coffee shop Over PT. Jeeva Work Corporation - Caecilia Kwarti Krist Marsiwi; Tantri Yanuar Rahmat Syah; Semerdanta Pusaka; Rhian Indradewa (Journal of Multidisciplinary Academic, 2019)
PT. Jeeva Works Corporation is a private company in hair cut style for man (Barbershop) and coffee shop especially men who are increasingly happy to be stylish and more aware of their appearance by choosing stylish hairstyles. In addition to lifestyle-related to the appearance of hair, the phenomenon of enjoying coffee at a coffee shop is currently also a part of the lifestyle. Harapan Indah, Bekasi was chosen as an initial location (company home base) after seeing the potential business of the existing Barbershop. The population of men aged in this area between 15 to 54 with 142.300 customers in 2020 on barbershop market share over 52.65% or 74.921 people. In addition, a potential Barbershop combined with coffee shop’s potential is also promising in this region. There are coffee shops and coffee enthusiast communities that to support PT. Jeeva Work with continue to grow. The company seized this opportunity by establishing a premium barbershop business which is provide technology to select hair models in menu form with re-modeling applications and provides rapid registration technology by developing an online registration application equipped with coffee shop facilities under Jeeva Barber Coffee brand. In this work, we purpose to analyze a level of investment feasibility. As an initial step, the preparation of the company’s, the cash flow was carried out. After that, an investment feasibility analysis was carried out by calculating and analyzing the parameters used which were ROI, P, BEP, PP, and IRR. The results of calculations and analysis of ROI, NPV, BEP, PP, and IRR on the company’s investment plan of 6.9 billion shows that the investment is feasible to run. ROI in the 5th year reached 55.16% > the target of 35%. The NPV calculated with WACC was 10.97%, showing a positive value, 2 years 5 months BEP < maximal target in BEP 3 years, 1st investment PP for 2 years 5 months and second investment for 2 years 1 month as expected < 3 years, IRR of 48.81% > minimum interest rate expected by investors of 13.13%